Implementation of recommendations in audit reports and their impact on municipal management - SUÁREZ SANTA CRUZ, Liliana Del Carmen (2020)
This study was mainly based on determining the influence on compliance of the correction of suggestions from the audit reports of the Office of Internal Control in the management of the Provincial Municipality of Lambayeque. The research approach is quantitative, explanatory and correlational, the design is non-experimental. The techniques of obtaining data, the survey, documentary analysis and direct observation were applied. The sample was made up of 17 public officials that comprise the Municipal Manager, Organic Unit Managers, Deputy Managers and Heads of offices of the entity. Regarding the reliability of the instruments, the Cronbach's alpha coefficient was applied, resulting in 0.925 and 0.932 for the "implementation of recommendations" and "municipal management" questionnaires, respectively. Among the results obtained, the internal control office during 2018 and 2019 issued a total of 35 recommendations, the municipality having (27) recommendations in a “pending” state, seven (7) in “process” and one (1) “Implemented”, determining that the public official, despite having been appointed by the Mayor to correct the suggestions, did not initiate the actions aimed at their implementation. Finally, the Spearman statistical correlation indicator was applied, resulting in 0.796; reason why it is affirmed that the fulfillment of the raising of recommendations of the control reports influences the management of the Provincial Municipality of Lambayeque.Keywords: Reports, Audit, Control, Recommendation, Management, Municipality.